Attitude assumed by nurses in regards to end of life decisions of people: Case of Costa Rica, 2011 - Andrade Espinales, Jerik (2012)
The research problem was to analyze what is the attitude assumed by nurses in regards to end of life decisions of people in Costa Rica during 2011. A quantitative exploratory and transactional methodology was developed, with a random sample and a subsample multistage taking into account the national hospitals Class A; obtaining a sample of 86 nursing professionals who completed a questionnaire. The obtained data was tabulated using a statistical package. The data demonstrated that although most of the participants were unfamiliar with the concept of end of life decisions, they related the said concept to the respect for the dignity, the rights and the autonomy of people in the same way they apply such ethical values when providing care. The research team concluded that the sampled nursing professionals favored the mentioned ethical values over their own personal ethics and morals.